Legionnaires' Disease: A Review. Issue 5 (September 2016) - Castillo, Natalia E.; Rajasekaran, Arun; Ali, Sayed K.
Abstract : Abstract: Almost 40 years ago, Legionella pneumophila was initially recognized as the cause of a major respiratory outbreak. Since the first description of Legionnaires' disease, surveillance schemes have been implemented worldwide; however, legionellosis is still an underdiagnosed and underreported entity. Legionella pneumophila causes a severe inflammatory pneumonia that primarily affects susceptible patients as a result of advanced age, underlying debilitating conditions, and immunosuppression. Organ-specific and extrapulmonary manifestations have also been described. Cooling towers and water systems in buildings and hospitals have been reported to be environmental reservoirs that commonly harbor this pathogen. Numerous prevention guidelines vary in scope, and effective surveillance and detection systems are required for early clinical intervention. Various diagnostic tests are available, but they do not offer the desired sensitivity. To date, urinary antigen testing is still the most rapid and inexpensive method used in the diagnosis of Legionella infection. Culture and isolation of L. pneumophila from clinical specimens are not as cost-effective as other diagnostic methods, but they continue to be the criterion standard for the diagnosis of Legionnaires' disease. The newer macrolides and respiratory tract fluoroquinolones are highly effective in the treatment of Legionella infection. Current understanding of Legionnaires' disease is crucial in the identification and management of major outbreaks.